Personal Networks : Wireless Networking for Personal Devices. - Jacobsson, Martin (John Wiley & Sons, 2010)
Written by experts in the field, this book describes the Personal Network architecture and its various components. This book focuses on networking and security aspects of Personal Networks (PNs). Given a single user, the authors propose an architecture for PNs in which devices are divided into one of two types of nodes: personal nodes and foreign nodes. Furthermore, the authors demonstrate the ways in which PNs can be formed in a self-organized and secure way, how they can be interconnected using infrastructure networks, how multiple PNs can be connected, and how their services and resources c.